Informational and analytical provision of operational searchactivity of the national police of Ukraine - Lysenko, Andrii; Lysenko, Iryna; Perevalova, Liudmyla; Haievaia, Oleksandra (State Research Institute MIA of Ukraine, 2020)
The activity of the operational units of the police in modern conditions, connected with the processing of a large number of information flows, includes work with large amounts of information. Taking it into account, a well-organized information-analytical provision of the operational-search activity is a significant factor which influence on the effectiveness of the fight against crime. However, practical experience shows that information-analytical provision in this area is not being carried out at a sufficient level due to the presence of certain organizational weaknesses. In this scientific work the content and essence of informational-analytical provision of Operational searchactivity of the National Police of Ukraine are considered, its problems are covered and ways of their solution are suggested.

Діяльність оперативних підрозділів поліції в сучасних умовах, пов'язана з обробкою великої кількості інформаційних потоків, включає роботу з великими обсягами інформації. З огляду на це, добре організоване інформаційно-аналітичне забезпечення оперативно-розшукової діяльності є суттєвим фактором, що впливає на ефективність боротьби зі злочинністю. Однак практичний досвід показує, що інформаційно-аналітичне забезпечення в цій сфері здійснюється не на достатньому рівні через наявність певних організаційних недоліків. У цій науковій роботі розглянуто зміст та сутність інформаційно-аналітичного забезпечення оперативно-розшукової діяльності Національної поліції України, висвітлено його проблеми та запропоновано шляхи їх вирішення.
Інформаційно-аналітичне забезпечення оперативно-розшукової діяльності національної поліції України
Keywords: operational searchactivity; operational searchinformation; sources of operational searchinformation; informational-analytical provision; National Police of Ukraine; оперативно-розшукова діяльність; оперативно-розшукова інформація; джерела оперативно-розшукової інформації; інформаційно-аналітичне забезпечення; Національна поліція України